Exploring The Impact of Kinesthetic Learning Strategies on Speaking Ability: A Study for Integrating Movement and English Language - Usuluddin, Usuluddin; Fikni, Zahratul; Husnu, Muhammad; Nadia, Riza (English Literature Study Program, Faculty of Humanities, Diponegoro University, 2024)
The purpose of this research was to investigates the effect of kinesthetic learning strategies on the speaking abilities of English learner. Employing a pre-experimental research design, the study involved 20 students from an FLC (Foreign Language Course) program. The research utilized quantitative methods, specifically oral tests, to measure the effectiveness of kinesthetic learning strategies. Data were collected through pre- and post-tests and analyzed using SPSS 22. The findings reveal a significant improvement in the speaking abilities of students who engaged in kinesthetic learning activities. The results of hypothesis testing showed a t-test value of 8.519 at p < 0.01, indicating that the null hypothesis was rejected and the alternative hypothesis was accepted. This suggests that kinesthetic learning strategies are effective in enhancing English speaking skills. The study concludes that integrating movement-based activities into language learning curricula can significantly benefit students' speaking proficiency. These findings support the adoption of kinesthetic learning strategies in language education, advocating for more dynamic and engaging instructional methods that cater to various learning styles.